Concevoir et aménager les espaces publics à Bruxelles - Benoit Moritz (Brussels Studies)
This text is a short account or summary of urban imaginations which have conditioned the formal view of the development of public space since the creation of the Brussels-Capital Region.It presents different periods which have constituted turning points and overlappings in the evolution of these imaginations.Through concrete examples, the text illustrates in particular how development practices for public space became recognised, at first through projects which were simply aimed at a better balance in the distribution of public space, and then progressively through projects which integrated questions regarding use and the architectural qualities of developments. The author discusses in particular the influence of the “neighbourhood contract” urban revitalisation tool in this evolution.The texts ends with the identification of new methodological challenges facing public spaces in Brussels, as regards the understanding of the different levels as well as project formalisation processes.